The Islamic Management Method Based on the Thinking of Sidek Baba - Hanapi , Mohd Shukri; Wan Khairuldin, Wan Mohd Khairul Firdaus (International Journal of Psychosocial Rehabilitation, 2020)
This working paper intended to examine and study the Islamic management method based on the thinking of an academic figure named Sidek Baba, a Professor of Education at the Kuliyyah of Education in Universiti Islam Antarabangsa Malaysia (UIAM). Hence, what is the Islamic management method based on the thinking of Sidek Baba. In order to answer this question, this paper was divided into three main discussion topics, namely the philosophy of Islamic management, application of ihsan (a sense of social responsibility borne from religious convictions) and humankind in the Islamic management method and lastly, fundamentals of the Islamic management method. These three elements were explored through an examination and analysis of several literary works by Sidek Baba. Findings showed that Islamic management philosophy is based on five main fundamentals of work according to Islam. Whereas, in the Islamic management method, there exist an integration of relations between humankind and Allah SWT (habl min Allah) or between ihsan/ humankind and inter-human relations (habl min al-Nas). Lastly, the study found that the core of the Islamic management method is piousness (taqwa) towards Allah SWT.